Analisis Regresi Logistik Faktor Kejadian Tuberkulosis Paru terhadap Kesehatan Lingkungan Masa Pandemi Covid-19 di Desa Penen Kabupaten Deli Serdang - Novrika Silalahi; Sri Sudewi Pratiwi (Jurnal Kesehatan Komunitas, 2021)
This research is very important to do because the incidence of pulmonary TB is still the biggest problem in public health, especially in Deli Serdang Regency. So that with this research can be obtained the highest factor of the incidence of pulmonary TB on environmental health. This study is to predict the model and detect the highest factors of pulmonary TB incidence on health such as home conditions consisting of ventilation, air humidity levels, lighting, residential density, and sewerage, clean living behavior or personal higiene, and personal nutritional status of TB sufferers. lungs during the Covid-19 pandemic. This research is a quantitative research using observational analytic method with a case control study design. Sampling using non-probability sampling technique, namely purposive sampling, namely patients with pulmonary TB in adults with a total sample of 70 people or 70 BTA (+) and as a control, namely 70 people who do not suffer from pulmonary TB or 70 BTA (-). The instruments used in data collection are questionnaires and observational sheets. Data analysis using logistic regression analysis model with modeling results Ln (P / 1-P) = 0.2422 – 19.972 Ventilation + 21.896 Air Humidity + 37.548 Illumination – 21.312 SPAL – 0.297 Personal Higiene. With OR of ventilation is 3.875, OR of lighting is 2.976, OR of SPAL availability of 1.067, OR of personal higiene of 0.743, OR of humidity of 0.678 and ventilation with OR of 3.875 as the variable  that has the highest OR value is the biggest factor in the results of this research.